Investigation of the matematical model of the multimensional automatic control system - Rimas, Jonas (Lietuvos matematikos rinkinys, 1998)
The mathematical model of the mutual synchronization system composed of n = 4p (p ∈ N) joined into a ring oscillators is investigated. The precise analytical expressions of the elements of the step responses matrix of the system are obtained.